Fundamentals of financial accounting - Phillips, Fred (McGraw-Hill/Irwin, 2013)
Fundamentals of Financial Accounting, presents an engaging, balanced, and appropriately paced analysis of the fundamentals of financial accounting. Its writing style makes it easy to read and understand, while the selection of real focus companies reinforces the relevance of accounting by introducing students to accounting and business activities in the context of their favourite companies. Balance between preparer and user orientations is achieved throughout the book, by studying both the accounting activities that take place inside the company, as well as evaluating their impact on decisions, and users outside the company. Topic coverage is paced appropriately for students new to accounting, and is thoroughly reinforced every step of the way with an ample variety of innovative pedagogical tools. Clearly understandable, relevant, and accessible, FFA is simply the most student-friendly financial book on the market and provides the tools for students to grasp financial accounting from the ground up.